106 Role of neuronal vs endothelial nitric oxide synthase in the coronary blood flow response to pacing. (16th May 2012) - Shabeeh, H; Melikian, N; Dworakowski, R; Casadei, B; Chowienczyk, P; Shah, A M
Abstract : Background: Endothelial nitric oxide synthase (eNOS) has been assumed to be the major source of nitric oxide (NO) regulating human coronary blood flow (CBF). In recent first-in-human studies with a neuronal NOS (nNOS)-selective inhibitor, we provided evidence that nNOS-derived NO regulates basal coronary blood flow whereas eNOS mediates increases in flow in response to the endothelial agonist, substance P. The present study aimed to investigate the effects of nNOS vs eNOS inhibition on coronary blood flow response to increased heart rate. Methods: We studied the effects of the nNOS-selective inhibitor, S-methyl-L-thiocitrulline (SMTC), and the non-selective NOS inhibitor, NG-monomethyl-L-arginine (L-NMMA) at doses previously shown to inhibit nNOS or both nNOS and eNOS, respectively. 18 patients already undergoing elective cardiac catheterisation for clinical reasons and found to have normal coronary arteries were included. An intracoronary Doppler flow wire was positioned in the coronary artery for measurement of blood flow velocity whereas coronary artery diameter was measured by quantitative angiography. An incremental pacing protocol that raised heart rate to a maximum of 150 bpm was undertaken in all patients via a temporary right atrial pacing wire. Pacing was performed in the presence of saline vehicle and then either L-NMMA or SMTC (one inhibitor per patient; n=9 each group). Results: SMTC (0.625 μmol/min) and L-NMMA (25 μmol/min) both reduced basal CBF to a similar extent (−22.8%±1.24% vs −26.8%±2.16%; n=9 each; p=NS). During saline infusion, CBF increased with atrial pacing from 58.7±9.90 to 87.4±17.3 ml/min (n=9, p<0.05). During L-NMMA, the increase in CBF was significantly blunted compared to that during saline (ΔCBF 17.7±4.54 ml/min vs 28.7±8.08 ml/min during saline; n=9, p<0.05 by 2-way ANOVA). In patients receiving SMTC, however, the increase in CBF with pacing was similar to that during saline (ΔCBF 36.5±6.05 ml/min vs 25.2±6.65 ml/min during saline; n=9, p=NS by 2-way ANOVA). SMTC and L-NMMA both reduced basal coronary artery diameter to a similar extent (n=9). L-NMMA blunted the pacing-induced increase in coronary artery diameter (n=9, p<0.05 vs saline vehicle) whereas SMTC had no effect (n=9, p=NS). Conclusion: These results suggest that increases in human coronary blood flow in response to incremental atrial pacing are mediated by eNOS-derived NO rather than nNOS-derived NO.